Symbols and Discursive Contestation of Presidential Election in Indonesia - Muhammad Nazaruddin; Ade Ikhsan Kamil; Faizul Aulia (Malikussaleh Social and Political Reviews, 2023)
This article will discuss how religion and identity become important factors in elections, especially in presidential elections. It means that this article will discuss how presidential candidates use religious symbols to gain support from religious voters, as well as the impact of the use of religious symbols in political campaigns. The discourse battle between the two candidate pairs shows the contestation between identity and popularity in Indonesian politics. Political identities based on religious symbolism, nationalism and populism can strengthen a candidate's political identity and attract support from certain groups. However, political popularity based on symbolism can trigger polarization and religious intolerance and ignore the interests of the wider community. Symbolism analysis shows how the two pairs of candidates use symbolism to strengthen their political identity. The Prabowo-Hatta pair used religious symbols such as pictures of the Kaaba and verses from the Koran in their campaign as a way to show they were religious leaders and true nationalists. Meanwhile, the Jokowi-Kalla pair uses symbols of nationalism such as the Red and White Flag and the Garuda Emblem as symbols of national pride and inclusive Indonesian identity. The 2014 presidential election in Indonesia shows the contestation between identity and popularity in Indonesian politics. Political identities based on religious symbolism, nationalism and populism can strengthen a candidate's political identity and attract support from certain groups. However, political popularity based on symbolism can trigger polarization and religious intolerance and ignore the interests of the wider community.